Correlation Between Autophagy and Collagen Deposition in Patients With Pelvic Organ Prolapse. Issue 3 (May 2018) - Zeng, Chunyan; Liu, Juan; Wang, Hailan; Zhou, Yan; Wu, Junwei; Yan, Guangrong
Abstract : Objectives: The aim of this study was to explore the link between autophagy and collagen metabolism in patients with pelvic organ prolapse (POP) by detecting the expressions of autophagy factors, collagen, desmin, cytokeratin, and vimentin. Methods: Histology of anterior vaginal wall and uterosacral ligament was assessed by hematoxylin-eosin staining in POP and non-POP control patients (n = 50 per group). Expressions of collagen types I and III, LC3II, beclin 1, and p62 were examined by Western blot analysis. Expressions of LC3, vimentin, desmin, and cytokeratin were detected by immunohistochemical staining. A linkage between the mean of LC3 integrated option density summation (IOD SUM) and POP clinicopathologic parameters including Pelvic Organ Prolapse Quantification (POP-Q) staging, age, body mass index, gravidity, and parity was analyzed by χ 2 test, respectively. Results: Compared with the control group, the following differences were found both in the vaginal wall and in the uterosacral ligament of the POP group: hematoxylin-eosin staining showed that collagen was more fragmented and disorganized. Expressions of collagen types I and III, LC3II, and beclin 1 were diminished, whereas the p62 level was elevated in Western blotting. Immunohistochemical staining showed that expression of LC3 was down-regulated, whereas vimentin level was increased. There were no significant differences in the expressions of desmin and cytokeratin in the 2 groups ( P > 0.05). Mean of LC3 IOD SUM was highly linked to the POP-Q stage in the POP group ( P < 0.05), whereas there was no significant correlation between the mean of LC3 IOD SUM and POP groups in age, body mass index, gravidity, and parity, respectively( P > 0.05). Conclusions: Autophagic activity is impaired in the POP group, which may relate to collagen deposition. Abstract : Impaired autophagy was linked to the collagen deposition in the pelvic organ prolapse group.